2018
DOI: 10.1186/s12890-017-0567-3
|View full text |Cite
|
Sign up to set email alerts
|

The associations between weight-related anthropometrics during childhood and lung function in late childhood: a retrospective cohort study

Abstract: BackgroundAn association between body weight in childhood and subsequent lung function and asthma has been suggested, but few longitudinal studies exist. Our aim was to explore whether weight-related anthropometric measurements through childhood were associated with lung function in late childhood.MethodsFrom an original nested case-control study, a cohort study was conducted, where lung function was measured in 463 children aged 12.8 years, and anthropometry was measured at several ages from birth through 12.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
13
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 47 publications
6
13
0
Order By: Relevance
“…The finding of lower lung function in obese subjects (by BMI) is in accordance with several previous studies [ 4 6 , 8 , 27 ]. However, in one of the previous studies there was a positive association between BMI and lung function in normal weight subjects [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…The finding of lower lung function in obese subjects (by BMI) is in accordance with several previous studies [ 4 6 , 8 , 27 ]. However, in one of the previous studies there was a positive association between BMI and lung function in normal weight subjects [ 27 ].…”
Section: Discussionsupporting
confidence: 93%
“…One possible explanation for the positive association between BMI and pulmonary function could be that subjects that are large already during childhood have larger lungs. This theory is supported by the findings of BYBERG et al [4] who found that from birth, weight-related anthropometric measures were positively associated with FVC and FEV 1 at 12.8 years of age. Central obesity, on the other hand, is often acquired over time and may primarily decrease lung volume, as it may restrict diaphragm movement and limit lung expansion [30].…”
Section: Discussionsupporting
confidence: 58%
See 1 more Smart Citation
“…BMI was used in this study in order to compare its results using the cutoff point that defines obesity (30kg/m 2 ) [9, 24] with those pointed out by FM and FMI. Previous studies have shown that the relationship between BMI and pulmonary function is not linear, due to the uncertainty between the percentage of FM and lean mass in the intermediate categories (normal/ overweight BMI), especially among adolescents and young adults [7, 10, 12, 13]. However, individuals with BMI ≥ 30kg/m 2 have lower pulmonary function attributed to adiposity excess [7, 13].…”
Section: Discussionmentioning
confidence: 99%
“…Analogous adaptations characterized by shorter limbs and sitting height are observed in both stunting and restrictive lung function 55 . The positive association between age at peak adiposity and higher FVC, FEV 1 and FEF 25-75 implies that IUGR, followed by rapid weight gain during childhood results in poor lung function 56 . Besides being shorter, stunted children have shorter leg length, resulting in a longer sitting-height-to stature ratio, which is known to influence population level differences in lung function 57 .…”
Section: Resultsmentioning
confidence: 99%